Pelatihan Peningkatan Pemahaman Logika dan Aplikasinya pada Pembuktian dalam Matematika untuk Dosen-Dosen Ilmu Komputer di PTS Bandar Lampung - Usman, Mustofa; W, Wamiliana; W, Warsono; Russel, Edwin (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
Logic is a very important knowledge in all fields, for example law, mathematics, language, and computer science. In mathematics, logic plays a role in providing ways or methods or steps in proving a theorem. In computer science, logic is very important because it is the mathematical basis of software: logic is used to formalize the semantics of programming languages and program specifications, and to verify the correctness of programs. However, the weakness is that logic is generally not taught in the curriculum in Computer Science and of course this is a gap that must be overcome if we want to build quality alumni. The problem is that lecturers generally do not understand the basic concepts of logic and their applications in mathematical proof methods. To overcome this weakness, a beginner activity was held, namely training in basic logic concepts and their applications in mathematical proof methods. This community service activity was carried out using lecture and discussion methods and exercises attended by computer science lecturers and students.